Correlation between Rheotens measurements and reinforcement of polymer nanocomposites in the injection molding compounder. (April 2015) - Battisti, Markus G; Friesenbichler, Walter; Duretek, Ivica; Guttmann, Peter
Abstract: The evaluation of the effectiveness of reinforcement of polymers and polymer nanocomposites(PNCs), in particular the improvement of Young's modulus, is made by performing standardized tensile tests. Structural and morphological characterizations typically are investigated using expensive techniques like transmission electron microscopy (TEM), X- ray scattering and sometimes also rheological analyses (rotational rheometry). The objective of this study is to generate faster and economically advantageous data to verify the quality of the produced PNC-compound in an on-line measurement system. Subsequently injection molded parts are processed by using the Injection Molding Compounder (PNC-IMC) "by only one plasticizing process". In comparison to the conventional compounding process, where the compound has to be pelletized and fed into the injection molding machine for the second plasticizing process, injection molding compounding combines these two processing steps. This paper shows first results and problems with the implementation of the Rheotens equipment into the concept of the IMC. Different processing techniques and various processing conditions were compared and the occurring effects were detected both with tensile testing and extensional melt rheology. Both, the increase of the Young's modulus by using layered silicates as nanofillersis compared to the virgin polypropylene and the correlation of the level of melt strength with Rheotens measurements is shown. These results give a good overview on both the possibilities and the limitations of the material pre-tests by the use of extensional rheology in the concept of the IMC for producing PNCs. Further studies to enable a fast and efficient way of estimating the level of reinforcement in PNCs by means of Rheotens measurements will be carried out towards industrial usability. Furthermore the verification of exfoliation and intercalation of the layered silicates in the polymer matrix using small angle X- ray scattering is planned.